Employer Branding Through Social Media: A Competitive Strategy to Attract Generation Z Job Seekers and Strengthen Corporate Reputation - Mareta Putri Hasyatamma; Dyah Santhi Dewi; Retno Widyaningrum (Publikasi Indonesia, 2025)
The purpose of this study is to explore Generation Z's perspective on utilizing social media information to apply for jobs via company employer branding. This quantitative study uses Least Square-Structural Equation Modeling (PLS-SEM) with a second-order research model to examine the influence of social media, employer branding, and competitive advantage on the interest in job applications and corporate reputation. Data was collected through a self-administered questionnaire using a 5-point Likert scale, distributed to 211 Generation Z respondents using the Lemeshow approach. Seven hypotheses were tested: (1) social media significantly affects job application interest; (2) employer branding significantly affects job application interest; (3) competitive advantage significantly affects job application interest; (4) job application interest significantly affects corporate reputation; (5) social media significantly affects corporate reputation; (6) employer branding significantly affects corporate reputation; (7) competitive advantage significantly affects corporate reputation. The study’s results indicate that all hypotheses were accepted, except for hypothesis (4). The practical implications include offering companies valuable insights on effectively using social media in employer branding to boost applicant engagement.